Proceedings of the First Asia/Pacific International Symposium on Instrumentation, Measurement and Automatic Control - Asia/Pacific International Symposium on Instrumentation, Measurement and Automatic Control (1st : 1991 : Shanghai, China); Dehui, Sun; Zongrui, Li; Hatakeyama, K. (Beijing : International Academic Pub., 1991)
14